Implementation of Pre-Enabling Family Program (Program Keluarga Harapan) to Support The Millennium Development Goals in Indonesia (Case Study in Kaloran Sub-District, Temanggung Regency of Central Java Province) - Lailul Mursyidah; Mardiyono Mardiyono; Bambang Santoso Haryono (Sekolah Pascasarjana Universitas Brawijaya, 2015)
One of the programs associated with the achievement of MDGs, especially in welfare and development of society is Conditional Cash Transfer (CCT), in Indonesia is the Pre-Enabling Family Program (Program Keluarga Harapan). In national level, this program was implemented since 2007 launched by the government aim to eradicate household-based poverty but in Kaloran Sub-District of Temanggung Regency held since 2012. This study intends to describe the policy on PEF program as conditional cash transfer program to eradicate poverty. This study found that PEF program implementation in the study area is good if seen from bureaucratic structures, resources, communication and disposition of the implementer. But in Temanggung Regency, the achievement progress of Millennium Development Goals is no difference before and after implemented PEF Program in 2012.Keywords: Conditional Cash Transfer,Â Millennium Development Goals, Poverty Reduction,Pre-Enabling Family Program